Krohn-Rhodes Complexity on Decision Rules - Gottinger, Hans W. (Advances in Social Sciences Research Journal, 2016)
The notion of ‘global rationality’ underlying the concept of ‘economic man’ as generally been accepted in normative economics has come increasingly under attack by those who strive for more realistic behavioral assumptions in economic reasoning. The critique applies particularly to various optimization programs that have been implemented in economics but that have been found only of limited use in realistic, complex situations. Herbert Simon deserves credit for having observed the limitation of global rationality and suggesting a modification of this program by introducing his concept of ‘bounded rationality’. To a great extent these ideas were advanced through studies of actual human thought processes. This paper relates the discussion on bounded rational decision rules to algebraic complexity of dynamic systems in the context of Krohn-Rhodes.